Tensile trading : the 10 essential stages of stock market mastery - Roze, Gatis N.; Roze, Grayson D. (Hoboken, New Jersey : John Wiley & Sons, Incorporated, 2016)
"A detailed 10-stage roadmap for investors to achieve stock market mastery with their own consistently profitable, high-probability investment system Tensile Trading provides a complete, step-by-step roadmap for investors of all levels, and coaches them on how best to organize the routines and strategies necessary to identify the market's strongest trading opportunities. History is proof that true mastery of the market begins with basic money management protocols, asset protection policies, and organized analysis techniques. With these crucial foundations in place, you can embrace a proven investment methodology, execute an effective trading plan, and develop a reliable system for profitable investing. Consistent, long-run investing success is a result of well-defined goals, carefully-constructed routines and an accurate understanding of the psychological challenges that all investors face. Set yourself up for success by implementing prudent money management and asset protection strategies Build a personalized Asset Allocation Profile--your own personalized investment methodology Construct a properly diversified portfolio using tools and techniques tailored for the modern market Learn to take control of your "Investor Self," limiting the impact of mental hurdles and emotional baggage Supercharge your financial analysis by employing proven routines and strategies A clear and proven approach easily tailored to fit your specific investing style, Tensile Trading distills the vastness of the financial markets into ten essential stages. It is designed to provide a comprehensive structure to your financial management efforts--helping you make smarter investment decisions, trade more efficiently, and consistently earn greater returns"--
Machine generated contents note: Preface A Message from Gatis A Message from Grayson Acknowledgments About the Authors Stage 1 Money Management Crafting Your Money Management Plan Personal and Appropriate Put It In Writing Thorough and Descriptive Methodology and Strategies Trading Tools and Money Management Rules Risk Tolerance and Protection Strategies Updated Regularly Becoming a Successful Investor The Importance of Asset Allocation Constructing Your Personal Asset Allocation Profile Core and Explore Minimizing Costs Asset Group Selection Asset Allocation Resources Correlation Coefficients X-Ray Magic Allocation Maintenance Stage 2 The Business of Investing 10 Invaluable Investing Lessons Lesson 1: Build Your Own Trading Place Lesson 2: Don't Skimp on the Tools of the Trade Lesson 3: Organization Breeds Profits Lesson 4: Harness the Power of a Curious Mind Lesson 5: Don't Try to Go It Alone Lesson 6: Keep Up with Legal and Tax Issues Lesson 7: Use Reliable Accounting and Investment Software Lesson 8: Foster an Entrepreneurial Tenacity and Work Ethic Lesson 9: Keep Estate Planning in Mind Lesson 10: Put It in Writing! Staying Committed on the Road The Investor's Quad Stage 3 The Investor Self The Five Levels of Investor Growth Investor Weaknesses Planning Roadblocks Deficiencies in Knowledge and Education Personal Psychological Baggage and Beliefs Execution Barriers Learn from the Professionals Your Daily Journal Stage 4 Market Analysis Permission to Buy Telescope-to-Microscope Approach Charting Indicators Organizing Your Analysis Common Misunderstandings The Market Stages and Technical Analysis Fundamentals Checklist for Stocks Fifty versus Fifty Stage 5 Routines Choosing Your Time Frame From Salesmen to Stock Traders Personal Peak Performance Daily, Weekly, Monthly, Annually Daily Routines Weekly Routines Monthly Routines A Day In the Life Stage 6 Stalking Your Trade Where to Look What to Look For How to Look When to Look Filters Cost Price Spread Timing Distribution and Earnings Dates Seasonality Human Nature and Overhead Supply Second-Opinion Resources The Sisters Strategy Revisited Mimic Wall Street's Masters The Base-Hit Investor Stage 7 Buying BATTLE V Methodology Pyramid Trading The Language of the Market Buy Routines Considering Alternatives Perfection Paralysis Commission-Free Mindset Invest Like You Drive It's All About Stress Control Stage 8 Monitoring You Bought It--Now What? Revisiting the Investor Self Market Monitoring Adjusting Stops Tools, Routines, and Charts Fundamentals Allocation Updates What Is Your Motivation? Stage 9 Selling Sell on Technicals, Not Fundamentals The Art of Selling Developing Your Selling System 1. Set a Target 2. Set a Trading Range 3. Set a Breakout Target 4. Follow the Patterns A Personal Selling Paradigm Price Relative Trend Signals Volume Momentum Bearish Patterns Personal Money Management Rules Mutual Fund Sell Signals Selling with the Sisters Sell-Side Pyramid Trading The Endowment Effect The Investor's Trail Stage 10 Revisit, Retune, Refine Cleanse and Move Forward Stage 1: Money Management Stage 2: The Business of Investing Stage 3: The Investor Self Stage 4: Market Analysis Stage 5: Routines Stage 6: Stalking Stage 7: Buying Stage 8: Monitoring Stage 9: Selling Stage 10: Revisit, Retune, Refine Personal Data Mining The Investor's Big Three Motivation Confidence Action Thoughts on Transformation About the Companion Website Index.
Includes index.
Description based on print version record.
Electronic reproduction. Ann Arbor, MI : ProQuest, 2016. Available via World Wide Web. Access may be limited to ProQuest affiliated libraries.
Keywords: Investments; Investment analysis; Speculation; Electronic books